PENGARUH PENGGUNAAN E-FILING DAN PEMAHAMAN PERPAJAKAN TERHADAP KEPATUHAN PENYAMPAIAN SPT TAHUNAN WPOP (Studi Pada WPOP Pekerja Bebas Di Kota Salatiga ) - Fadillah Achmad Resandi; Ika Kristianti (STIE Atma Bhakti, 2021)
The purpose of this study to determine the effect of using e-filing and understanding of taxation on compliance of annual taxpayer reporting of the individual taxpayer in the Salatiga. The population of this research is non-employee individual taxpayers who are registered in KPP Pratama Salatiga. The sample used is 100 respondents and data collection techniques using an incidental sampling method. The questionnaires were distributed using google form and given directly to respondents. The collected questionnaire data was tested with validity, reliability, and classical assumption tests. Hypothesis test using the T-test with multiple linear regression models. The results of this study indicate that (1) the use of e-filing has a positive effect on compliance with the annual taxpayer reporting of non-employee individual taxpayers in Salatiga. (2) Understanding taxation has a positive effect on compliance with the annual taxpayer reporting of non-employee individual taxpayers in Salatiga.